Immunodeficiency - Metodiev, Krassimir (IntechOpen, 2012)
This book reflects a major medical problem which is still under thorough studies. There is a number of clinical cases corresponding directly or indirectly to a certain alteration of the immune system, thus leading to various pathologic conditions. The unique defense, what humans have with their immunity, is rather often affected by infections, tumor processes, organ, tissue and cell transplantation, allergy, autoimmune processes, as well as different influences by the environment. The Book has an international team of authors all contributing to the investigation of the questions of what, why, how, when and where the immune system deviates from its normal function, what clinical consequences are manifested and is there a way to prevent and treat the immunodeficiency cases. This Book can be a very good teaching tool for students and post-docs of medicine and biology, but it also provides updated information for the colleagues immunologists, microbiologists, virologists, chemotherapists, oncologists, hematologists, transplantologists and pathologist.